SCIENTIFIC AND PEDAGOGICAL BASES OF INCREASING MEDIA LITERACY OF PRESCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2025)
This scientific article analyzes the theoretical and practical aspects of the formation and development of media literacy in preschool children. The study examines the essence of the concept of media literacy, the psychological features of the preschool age and the influence of the digital information environment on children's development. It also reveals on a scientific basis the pedagogical conditions, methods and tools for improving media literacy in preschool education organizations, game technologies and the importance of pedagogical and parental cooperation. The results of the study show that the systematic introduction of elements of media literacy in the preschool education process contributes to the formation of children's conscious perception of information, critical thinking and digital culture.